If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -1 = 5x + 3x + -8 Reorder the terms: -1 + 1x = 5x + 3x + -8 Reorder the terms: -1 + 1x = -8 + 5x + 3x Combine like terms: 5x + 3x = 8x -1 + 1x = -8 + 8x Solving -1 + 1x = -8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -1 + 1x + -8x = -8 + 8x + -8x Combine like terms: 1x + -8x = -7x -1 + -7x = -8 + 8x + -8x Combine like terms: 8x + -8x = 0 -1 + -7x = -8 + 0 -1 + -7x = -8 Add '1' to each side of the equation. -1 + 1 + -7x = -8 + 1 Combine like terms: -1 + 1 = 0 0 + -7x = -8 + 1 -7x = -8 + 1 Combine like terms: -8 + 1 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| -3z+8+(-12z)=-2 | | 5x+12+x+3x-2=180 | | d+r= | | 2k+5/3+8/3=1/3 | | -3z+8+(-12z)=-12 | | 4x^2-2x+7=0 | | 2x+7=18-20x | | 5g+4(-5+3g)=-1-g | | 2.65=1.8b+3-2.5b | | 2x+5=10x-5 | | .6*x=10 | | 2k+5/3+2/2/3=1/3 | | 2x+4(x-5)=11 | | -0.9b-1.64b=2.794 | | -2.3+0.7x=1+0.6x-1.8x-6.53 | | 5x+5=2x-3 | | -1v+1=-2v+4 | | 15x-4y=6 | | -2.3+0.7x=1+0.6-1.8x-6.53 | | (7+6)2= | | 4x-4+1=21 | | -2.9x-1.5=5.1848+0.3x | | 4(x-4)=40-4x | | y+7=56 | | 36m^5n^2+24m^2n^3-18m^6n= | | 35m^5n^2+24m^2n^3-18m^6n= | | 5x+7=14-13x | | 2y+1=y-1 | | 0.768-b-0.4b=b+1.728 | | x^3-x^2-54x+144=0 | | .02x^2+0.1x-2=0 | | 5x+5-3x=14+3 |